Fate of trace elements in Oxygen Carrier Aided Combustion (OCAC) of municipal solid waste. (1st March 2022) - Staničić, Ivana; Backman, Rainer; Cao, Yu; Rydén, Magnus; Aronsson, Jesper; Mattisson, Tobias
Highlights: Bottom and fly ashes sampled over a period of 38 days. Detailed characterization of ilmenite particles using X-ray Photoelectron Spectroscopy. Effect of bed material, temperature and reduction potential investigated. Zn is incorporated in the Fe-rich ash layer in ilmenite particles. Accumulation of Cu observed over time and limited interaction detected with Pb. Abstract: Oxygen Carrier Aided Combustion is a novel fluidized bed concept for burning waste. This study analyzed solid samples from an industrial OCAC application using municipal solid waste and the oxygen carrier ilmenite. The presence of oxygen carriers impacts the ash chemistry, which can influence corrosion and ash characteristics. By investigating samples obtained from industrial applications, unique and highly relevant information on the solid-state chemistry and the fate of important elements can be obtained. In total, 20 bottom ashes and 17 fly ashes were sampled over a period of 38 days. In a preceding study, the surface interaction between ilmenite and Zn, Cu and Pb was investigated. In this paper, the distribution of these elements throughout the particle cross-section and the influence of residence time has been studied using XRD, SEM-EDX and XPS. The results show that Zn is incorporated in the Fe-rich ash layer over time in the form of Zn ferrites, while Cu accumulates inside the ilmenite particles with time, and Cr is enriched in the magnetically separated bottom ash. Low concentrations of Pb were detected in the bottom ashes, suggesting that a significant part is released in the gas phase. The influence of temperature, bed material and reduction potential were evaluated using multicomponent, multiphase equilibrium calculations. It is shown that an ilmenite bed is less prone to form melts in comparison to a bed of silica sand and that the addition of sulfur could decrease the volatilization of Pb.